2012
DOI: 10.1258/ebm.2011.011269
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal permeability is an intrinsic factor in susceptibility to dextran sulfate sodium-induced colitis in rats

Abstract: We investigated differences in the pathogenesis of dextran sulfate sodium (DSS)-induced colitis between two inbred rat strains, Wistar King A Hokkaido (WKAH) and Dark Agouti (DA) rats, to determine the intrinsic factors responsible for the development of colitis. DSS exposure exacerbated the clinical symptoms such as body weight loss, stool consistency and rectal bleeding in DA rats rather than that in WKAH rats. Additionally, the average survival was shorter in DA rats than in WKAH rats. The expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
0
17
1
1
Order By: Relevance
“…Consequently, translocation of ZO-1 and thereby the associated contraction of cytoskeletal actin is thought to play an important role in the regulation of epithelial barrier function (Umeda et al, 2006). We did not observe LPS-dependent effects on the total protein level of different tight junction proteins, such as ZO-1, occludin and claudin-1, but it is known that it is mainly not the expression level but the expression pattern of tight junction proteins that determines epithelial permeability (Iwaya et al, 2012). Not only the epithelial cell layer itself, but also the overlying mucus barrier, which consists of large glycoproteins called mucins, is extremely important for the intestinal barrier function.…”
Section: Discussionmentioning
confidence: 59%
“…Consequently, translocation of ZO-1 and thereby the associated contraction of cytoskeletal actin is thought to play an important role in the regulation of epithelial barrier function (Umeda et al, 2006). We did not observe LPS-dependent effects on the total protein level of different tight junction proteins, such as ZO-1, occludin and claudin-1, but it is known that it is mainly not the expression level but the expression pattern of tight junction proteins that determines epithelial permeability (Iwaya et al, 2012). Not only the epithelial cell layer itself, but also the overlying mucus barrier, which consists of large glycoproteins called mucins, is extremely important for the intestinal barrier function.…”
Section: Discussionmentioning
confidence: 59%
“…Dietary Dex possibly affected the population and functions of immune cells. We previously demonstrated that IFN-γ mRNA expression did not increase in early phase of DSS-induced colitis in an inbred strain originated from Wistar strain [39]. In contrast, IL-1β mRNA expression increased even in the early phase of the colitis.…”
Section: Discussionmentioning
confidence: 91%
“…Previous reports have demonstrated that DSS treatment impairs the TJ barrier and/or structure of the rat colon and intestinal Caco-2 cells (26,27), indicating the direct effect of DSS on intestinal epithelial cells. DSS is thought to influence the signaling pathways leading to TJ barrier regulation in epithelial cells, as the expression and localization of TJ proteins are regulated by various signaling pathways.…”
Section: Discussionmentioning
confidence: 93%